Work - Life Balance and Employee Health : A Cross-Sectional Analysis of Manufacturing and Service Sectors - Mittal, Kshitija; Singh, Karminderjit; Sharma, Geetika (Prabandhan: Indian Journal of Management, 2017)
Work - life balance and its association/impact have been studied separately in different settings/industries. In the present study, we performed a cross-sectional analysis of the impact of work-life balance on employee health in the manufacturing as well as service sectors. Responses were sought from 150 middle and senior level employees working in various manufacturing and service sector organizations in the North-Western region of India through a structured questionnaire. This sector-wise research examined the interrelationships amongst various demographic variables, health, and work-life balance. The results substantiated that pressure from work causes an imbalance in life, which leads to several health problems including stress. The results also revealed the commonalities and differences in work-life balance across the two sectors.